EXPERIMENTAL STUDY OF COMPRESSIVE STRENGTH OF MORTAR K-50 WITH ADDITIVE MATERIALS FLY ASH AMP BAULA PT. SATRIA JASA SENTOSA - Aryadi, Armin; Kadarinawati, Ana; Yatjong, Isramyano (Politeknik Negeri Jakarta, 2025)
The application of mortar is generally intended for non-structural work such as wall plastering, brick adhesive, mortar on river stone foundations, plastering for ceramic installation, brick, paving block, concrete pipes, rosters, and others. Mortar is widely used as a construction material because its ingredients are easily obtainable, and it is simple to work with. The quality of mortar is influenced by its constituent materials, the use of ingredients that meet the required specifications will result in good quality mortar. This study aims to determine the physical characteristics of fine aggregate and fly ash on K-50 mortar and the effect of adding fly ash on the compressive strength of K-50 mortar. The research methodology used is experimental, where experiments are conducted by manipulating or controlling natural conditions through the creation of artificial conditions. The test results of fine aggregate characteristics, including sieve analysis, density, specific gravity, water content, and quartz sand waste meet the specifications and suitable for use in mortar mixtures. The characteristics of fly ash obtained specific gravity of 2.436, loose content weight of 1.576 gr / cm3 and compacted content weight of 1.665 gr / cm³. The effect of adding fly ash on the compressive strength of K-50 mortar was examined for mixture ratios of 1Pcc: 3Psr, 1Pcc: 4Psr, 1Pcc: 5Psr, 1Pcc: 6Psr fly ash addition of 5% and 10%. The results show that the greater the amount of fly ash used, the higher the compressive strength of the mortar. The maximum compressive strength for 5% fly ash is 128.80 kg/cm², while for 10% fly ash it is 179.20 kg/cm², both achieved at the 1Pcc: 3Psr mixture ratio.